The Impact of Neutrophil Recruitment to the Skin on the Pathology Induced by Leishmania Infection - Passelli, Katiuska; Billion, Oaklyne; Tacchini-Cottier, Fabienne (Frontiers in Immunology, 2021)
Leishmania (L.) are obligate intracellular protozoan parasites, that cause leishmaniases, a spectrum of neglected infectious vector-borne diseases with a broad range of clinical manifestations ranging from local cutaneous, to visceral forms of the diseases. The parasites are deposited in the mammalian skin during the blood meal of an infected female phlebotomine sand fly. The skin is a complex organ acting as the first line of physical and immune defense against pathogens. Insults to skin integrity, such as that occurring during insect feeding, induces the local secretion of pro-inflammatory molecules generating the rapid recruitment of neutrophils. At the site of infection, skin keratinocytes play a first role in host defense contributing to the recruitment of inflammatory cells to the infected dermis, of which neutrophils are the first recruited cells. Although neutrophils efficiently kill various pathogens including Leishmania, several Leishmania species have developed mechanisms to survive in these cells. In addition, through their rapid release of cytokines, neutrophils modulate the skin microenvironment at the site of infection, a process shaping the subsequent development of the adaptive immune response. Neutrophils may also be recruited later on in unhealing forms of cutaneous leishmaniasis and to the spleen and liver in visceral forms of the disease. Here, we will review the mechanisms involved in neutrophil recruitment to the skin following Leishmania infection focusing on the role of keratinocytes in this process. We will also discuss the distinct involvement of neutrophils in the outcome of leishmaniasis.